CASE STUDY: ORGANOPHOSPHATE POISONING – ATROPINE-INDUCED PSYCHOSIS IN INTENSIVE CARE UNIT PATIENT - PORANKI, VATHSALYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Organophosphate compounds are used as commercial insecticides and applied as aerosols or dust. Consuming these compounds intentionally or unintentionally lead to dangerous conditions even to fatality. The most common obstacle in treating organophosphorus poisoning is the availability of sufficient medical care, equipment to provide proper emergency care observed in rural areas where there is a lot of gap between intensive care and acute care. Atropine use is as an antidote in organophosphorus poisoning. The dose of atropine mainly depends on the organophosphorus toxic doses. Atropine is a competitive antagonist of acetylcholine at the muscarinic postsynaptic membrane. Atropine blocks all the muscarinic effects in the body. This study presents a case of organophosphorus poisoning treated with atropine leading to atropine psychosis. Patient’s conditions, outcomes, and improvements are studied.